Fluorocarbon: Scrap Management Process Project title: Design and implement a process to monitor and reduce scrap - Vanhaelst, David (2007)
This dissertation describes a ten week internship at Fluorocarbon. There were two main goals in the project set for the internship. First of all, design and implement a system to monitor the scrap levels in all stages of production. Second, using these data, come up with ways to reduce the scrap. A generic framework should be developed that can be rolled.